PERAN ROHANI ISLAM (ROHIS) SAHDAN HIJJRAN SMA NEGERI 1 KERUMUTAN DALAM MEMBENTUK POTENSI ANGGOTANYA - Fery Kurniawan; Yoskar Kadarisman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
School is the highest formal education among students. It does not only contain academic activities, but also contains non-academic and extracurricular activities. Academic activities as in general are indeed applied in the teaching and learning process between students and teachers. Non-academic activities are indeed a distinct advantage for schools, because they can foster potential other than academics. Non-academic activities or the so-called extracurricular play an important role in the formation of the various potentials of each student. The world of school organizations, especially the high school level, has actually described people's lives. Where there is a class system, regeneration, and regeneration. So when students are fluent in school organizational life, it is certain that they will also have an advantage in society. As described by Sahdan Hijjran, an Islamic institution that has been able to shape the potential of its members well. through the school environment, each member of Sahdan Hijjran has been able to spread and mingle with other extracurricular members, even becoming a leader. Of course, this has become a form of implementation of the potential of its members. This research will use a qualitative method and involve 4 informants who are the core administrators of Sahdan Hijjran for 2 periods, and 1 key informant who is the coach of Sahdan Hijjran. Determination of informants using purposive sampling technique. The author's data collection techniques did by interview, observation and documentation. The purpose of the results of this study shows that there is a role grown by Sahdan Hijjran in shaping the potential of each member. The role of Sahdan Hijjran is as a shaper of noble character, good character, and superior achievement. Keywords: Islamic Spirituality, Role, Formation, Potential